SURVEI TINGKAT KEBUGARAN JASMANI PEMAIN BOLAVOLI PUTRA U-16 NANGGALA SURABAYA - SABIL KELANA WIDY, TEGAR (Jurnal Kesehatan Olahraga, 2016)
Physical fitness is a person’s body’s ability to perform daily without causing significant fatigue, so that the body still has energy reserves to cope with the additional workload. Not experience fatigue with means the point is that once a person’s doing and activity or event, still have enough passion and energy to enjoy there spare time and for other sudden. The purpose of this study was to determine how the level physical fitness of volleyball player men’s U16 Nanggala Surabaya. This type of research is a quantitative descriptive research. The population in this study is a volleyball player men’s U16 Nanggala Surabaya totaling 30 people. While the sample in this study amounted to 12 people with the characteristics of male average age was 15-16 years. Following the exercise routine, the competition or championships. How to obtain data using TKJI test conducted one meetings. From the analysis results using computer application SPSS (Statistical Package for the Social Science) versions 21 and manual calculation can be discovered that the average physical fitness of player U16 men’s volleyball Nanggala Surabaya is 12,9167 with a standar deviation of 1, 67649. Lowest value is a 16 and highest value is 22. While the percentage of the results physical fitness of player volleyball men’s U16 Nanggala Surabaya can be concluded, that athlete who fall into the category of less absolutely no of 0%. The athelete who fall into category of medium is 4 people or 33,33 %. Athelete who fall into category good as many 7 people or 58,33 % and the good once is a 1 people or 8,33 %. Keyword : Survey, Level of physically fitness, volleyball.